Accurate geometrical restraints for Watson–Crick base pairs. Issue 2 (9th April 2019) - Gilski, Miroslaw; Zhao, Jianbo; Kowiel, Marcin; Brzezinski, Dariusz; Turner, Douglas H.; Jaskolski, Mariusz
Abstract : Revised geometrical parameters are proposed for the Watson–Crick pairs of nucleobases, for use as restraints in modeling and refinement of the structures of nucleic acids. Accurate values of these parameters were derived (and compared) from small‐molecule Cambridge Structural Database structures, from super accurate ultrahigh‐resolution nucleic acid structures in the Protein Data Bank, and from quantum mechanical calculations. The effect of base pairing on the molecular geometry of the nucleobases is also investigated. Abstract : Geometrical restraints provide key structural information for the determination of biomolecular structures at lower resolution by experimental methods such as crystallography or cryo‐electron microscopy. In this work, restraint targets for nucleic acids bases are derived from three different sources and compared: small‐molecule crystal structures in the Cambridge Structural Database (CSD), ultrahigh‐resolution structures in the Protein Data Bank (PDB) and quantum‐mechanical (QM) calculations. The best parameters are those based on CSD structures. After over two decades, the standard library of Parkinson et al. [(1996), Acta Cryst . D52, 57–64] is still valid, but improvements are possible with the use of the current CSD database. The CSD‐derived geometry is fully compatible with Watson–Crick base pairs, as comparisons with QM results for isolated and paired bases clearly show that the CSD targets closely correspond to proper base pairing. While the QM results are capable of distinguishing between single and paired bases, their level of accuracy is, on average, nearly two times lower than for the CSD‐derived targets when gauged by root‐mean‐square deviations from ultrahigh‐resolution structures in the PDB. Nevertheless, the accuracy of QM results appears sufficient to provide stereochemical targets for synthetic base pairs where no reliable experimental structural information is available. To enable future tests for this approach, QM calculations are provided for isocytosine, isoguanine and the iCiG base pair.